Utilization of Ulva spp. in Biscuit Formulation: Feasibility Studies at the Household Scale. Issue 1 (1st February 2022) - Kusumawati, R; Sinurat, E; Sihono; Fransiska, D; Subaryono; Nurhayati; Purnomo, A H; Utomo, B S B; Basmal, J
Abstract: Green seaweed Ulva spp. contains dietary fiber and bioactive compounds and can be used as raw material for biscuit products. People from toddlers widely consume biscuits to the elderly. The technique of making biscuits is easy and does not require significant capital. The addition of 1% Ulva flour in biscuit formulations reported could control blood sugar levels. This study aimed to calculate the feasibility of Ulva biscuits production on a household scale with variations in 1 and 2 kg production capacity in 3 replications. The results showed that the yields were 74.94 to 77.02% and were not significantly different. The nutritional contents were also not significantly different, i.e., 2.89 to 3.53% of water content, 2.84 to 3.14% of protein content, 42.61 to 45.03% of fat content, 46.80 to 49.59% of total carbohydrates, and 41.71 to 45.57% of reducing sugar. Based on the calculation of business feasibility with a financial approach, the break-even point (BEP) value will be achieved if a minimum production of 2 batch processes per day is carried out with a production capacity of 15 kg of flour per batch and a working period of 25 days per month. The net present value (NPV) will be reached 85.9 million rupiahs, and the payback period (PP) will be achieved in 14 months.